Iron‐Catalyzed Direct C–H Arylation of Heterocycles and Quinones with Arylboronic Acids. Issue 24 (24th June 2013) - Deb, Arghya; Manna, Srimanta; Maji, Arun; Dutta, Uttam; Maiti, Debabrata
Abstract: The arylation of C–H bonds to generate heteroaryl–aryl (Het–Ar) and arylated quinone (Quin–Ar) compounds has received great attention to achieve sustainable goals in synthetic chemistry. Despite significant advances, arylation of a broad range of Het–Ar and Quin–Ar derivatives remains a challenging task. Herein, a variety of heterocycles are arylated by using arylboronic acids in the presence of catalytic amounts of inexpensive Fe(NO3 )3 . The C‐arylated quinone compounds can be prepared by reacting arylboronic acids with either quinone or hydroquinone. The present method is operationally simple, scalable, does not require prefunctionalization of the heterocycle or quinone, and can tolerate a wide variety of functional groups in the coupling partners. These qualities are expected to render this method attractive for academic and industrial use. Abstract : Direct C–H arylation of a variety of heterocycles and quinones with arylboronic acids has been developed. An inexpensive iron catalyst, Fe(NO3 )3, and a co‐oxidant, persulfate, were used in air. The protocol is applicable for large‐scale synthesis and is expected to find application as a result of its operational simplicity.